The Revision of the Array of “Confirmation of Something Similar to Its Contradiction” and the Role of Recognizing It in the Interpretation of the Qur'an - sayyed Mahmud Tayeb Hosseini; Abbas Rahimloo (آموزه‌های قرآنی, 2020)
One of the arrays of innovative knowledge that makes speech beautiful and captivating with aberrations and grammatical lawlessness is the technique of “Confirmation of something similar to its contradiction’. This article, after studying the explorations of literary men in the history of rhetoric, is going to uncover the mechanism of this figure of speech and the semantic implications of its types. A theoretical exploration of the process of this array reveals that the function of this technique in artistic propositions can be such as emphasis, exaggeration, and sometimes suspension of the impossible and quasi-literary argument. By these achievements, it becomes clear that if an interpreter in the prominent examples of this array in the Qur'an only suffice to the efforts of some scholars, the semantic implications and aesthetic manifestations of the verses will not be revealed and sometimes slip for interpretation. Familiarity with this rhetorical approach sometimes prevents the unreasonable carrying of words over seemingly meaningless ones, and also helps in the integrated interpretation of verses with this literary technique.